(untitled) (Research, Society and Development, 2021)
Hyptis marrubioides Epling is a species of the Brazilian cerrado traditionally used to treat gastrointestinal and cutaneous infections, pain, and cramps. The use of visible and ultraviolet C (UVC) radiation is a promising strategy to optimize the production of the bioactive metabolites. Therefore, the effect of the spectral quality of light on the production of metabolites was evaluated in H. marrubioides callus. The callus was inoculated on MS medium with 50% of the salt concentration containing 2 mg L-1 naphthaleneacetic acid (NAA) and 1 mg L-1 benzylaminopurine (BAP). The callus cultures were exposed for 20 days to the spectral qualities of white light, blue, red, and blue + red as well as to darkness. In addition, the callus cultivated under white light were exposed to UVC on the 21st day for 0, 30, 60, 120, and 240 seconds. The exposure of H. marrubioides callus to blue light negatively affects the synthesis of phenolic compounds. Red light stimulates the synthesis of caffeic acid and luteolin. Darkness was the best condition among those studied because it was associated with the increased accumulation of caffeic acid, chlorogenic acid, rosmarinic acid, and luteolin. The exposure of H. marrubioides callus cultivated under white light to UVC radiation promoted an increase in the synthesis of chlorogenic acid, ferulic acid, rosmarinic acid, and luteolin.